Subaru/IRCS L-band spectro-polarimetry of the HD 142527 disk scattered light. (14th June 2022) - Honda, Mitsuhiko; Tazaki, Ryo; Murakawa, Koji; Terada, Hiroshi; Kudo, Tomoyuki; Hattori, Takashi; Hashimoto, Jun; Tamura, Motohide; Watanabe, Makoto
Abstract: Spatially resolved L -band spectro-polarimetric observations were carried out toward a protoplanetary disk around the Herbig Fe star HD 142527 using the polarimetry mode of the InfraRed Camera and Spectrometer on the 8.2 m Subaru Telescope. The 2.9–4.1 μm polarimetric spectra of the bright central source and the scattered light at a distance of 0^′ ′_.78 from the center toward the PA ∼ 290° were obtained using the AO188 adaptive optics system. The polarization spectra of the central region show no significant evidence of the polarization which is expected with the (non-aligned) hot dust emission near the central star, while the disk scattered light spectra shows linear polarization of \!\! 10%, which is consistent with the nature of scattered light. In addition, the polarization PA of ∼20° is also geometrically consistent with the scattered light from the central region. We also derived the flux density spectra of each region and confirmed the 3 μm water-ice absorption feature in the scattered light spectra, which is consistent with the findings in Honda et al. (2009, ApJ, 690, L110). By comparing the model predictions by Tazaki et al. (2021b, ApJ, 921, 173), we estimated the grain properties of the extracted disk region. Assuming the power-law size distribution of silicate and ice, the maximum grain size a max of 3 μm and fractional ice abundance relative to Pollack et al. (1994, ApJ, 421, 615) ( f ice ) of ∼0.1 is inferred, which is consistent with the finding by Tazaki et al. ( 2021b, ApJ, 921, 173).